(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
The web portal of placement and training cell provides various placement and training related activities performed in the placement and training cell. This system have admin login and student login. The admin has overall rights of the system. The student can upload his/her details after registration and also student can able to see the upcoming drives which was uploaded by admin. The student can learn various programming languages through this web application. Where this system also provides mcq test for students. This system manages student data as well as company details efficiently. The admin posts the company details, number of eligible students attending the company and placement related examination through the system. student can view the details of the company through the placement and training cell system. This placement and training cell system is beneficial for college students.